Respond quickly and effectively! Components of the military health surveillance system in natural disasters: A qualitative study - Maryam Naderi; Ali Reza Khoshdel; Simintaj Sharififar; Arasb Dabbagh Moghaddam; Armin Zareiyan (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The systematic collection, analysis, and interpretation of health data by health surveillance systems provide timely and comprehensive surveillance of public health, identification health priorities, and, consequently, a quick and timely response to reduce damage during natural disasters. Since military forces appear as first responders at the scene of accidents, the present study aimed to identify the components of the military health care system during natural disasters. MATERIALS AND METHOD: Qualitative data collected through semi-structured interviews were analyzed via the conventional content analysis approach to identify the components of the military health care system in natural disasters. The participants consisted of 13 experts who were experienced in providing health services in the military and the civilian health care system during natural disasters in January 2022 to June 2022. RESULT: The identified components were classified into four main categories, namely, pre-requisite components (comprehensive health care, defined position, and providing information), driving components (system efficiency, effective communication), operational components (contingent performance, effective response), and promotional components (purposeful support, pre-disaster preparation). CONCLUSION: In conclusion, the military health surveillance system is a cooperative service for the national health system in which data is essential for making decisions on health and treatment measures during disasters. This study-by identifying four categories of the important components in the design, implementation, and development of the military health surveillance system-provides a comprehensive view of an appropriate and evidence-based military surveillance system in disasters.